The Application of Lamda-Mu-Rho Seismic Inversion for Conglomerate Reservoir Characterization in Melandong Field, Northwest Java Basin - Muhammad Ridha Adhari (PSI-Aceh, 2016)
Lamda (λ) Mu (μ) Rho (ρ) seismic inversion method has been applied to identify the distribution ofconglomerate reservoir in Melandong Field, Northwest Java Basin. This research used 3D pre-stack timemigration seismic dataset with one well data and a checkshot data. A sensitivity test analysis was done tosee the validity of the dataset and well seismic tie has been applied before generating a background modelfor the inversion processes. The outcomes of this research show that Lamda Rho ( λρ) inversion can be usedto detect the presence of hydrocarbon in a conglomerate rock and it is shown by value ranging between 33-39 (GPA*(Gr/cc)). Besides that, Mu Rho (μρ) inversion can indicate the rock type and it shows thatconglomerate has higher value (26 – 32 (GPA*(Gr/cc)) than claystone (20-26 (GPA*(Gr/cc)). By combiningboth Lamda-Rho and Mu-Rho inversion results, the distribution of the reservoir rock and hydrocarbon caneasily be detected and mapped.